Interventional treatment of a huge hepatic artery aneurysm as an unusual cause of upper gastrointestinal bleeding - Se Hwan Kwon; Jehong Yoon; Seung Yeon Noh; Hyung Joon Ahn; Joo Hyeong Oh (Society of Gastrointestinal Intervention, 2020)
A 61-year-old man presented to our hospital with abdominal pain and melena. He showed no obvious source of bleeding on gastroduodenoscopy. Computed tomography and conventional angiography revealed a huge aneurysm arising from the common hepatic artery. The aneurysm was embolized using coils. The procedure was uncomplicated, and the patient was discharged from the hospital 5 days after admission. Herein, we present the case of a rare huge hepatic artery aneurysm (5.7 × 6.0 cm in size) that caused abdominal pain and upper gastrointestinal bleeding.